Analisis Sistem Manajemen Proyek Menggunakan Prototype dan ISO 25010 pada PT Teknologi Informatika Solusindo - Gathot Ari Sadewo; Bagus Maulana Muhammad; Chairul Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Effective project management requires an integrated system to support team coordination, task monitoring, and efficient information delivery. At PT Teknologi Informatika Solusindo, project monitoring has been conducted through separate processes, making it difficult to track work progress and ensure effective collaboration. This study aims to design and develop a web-based Project Management Dashboard using the Prototype development method, which emphasizes iterative system refinement based on user feedback and operational requirements. The application provides features for project tracking, task management, progress visualization, and centralized reporting to improve monitoring and decision-making. System quality was evaluated using the ISO/IEC 25010 software quality standard through a Likert-scale questionnaire administered to 28 respondents representing potential users. The evaluation assessed key quality characteristics, including usability, functional suitability, and overall user satisfaction. The results showed that the developed system achieved an average score of 93%, which falls within the Very Good category. These findings indicate that the application successfully meets users' operational needs by providing a structured, integrated, and user-friendly platform for project management. The implementation of the Project Management Dashboard is expected to improve project supervision, enhance communication among team members, and support more efficient project execution. Therefore, the proposed system is considered suitable for implementation in the operational environment of PT Teknologi Informatika Solusindo.